Mortality, rehospitalizations and costs in children undergoing a cardiac procedure in their first year of life in New South Wales, Australia. (15th August 2017) - Lawley, Claire M.; Lain, Samantha J.; Figtree, Gemma A.; Sholler, Gary F.; Winlaw, David S.; Roberts, Christine L.
Abstract: Background: Cardiac procedures are part of management for many children with congenital heart disease (CHD). Using population health data, this study explores health outcomes of children undergoing a cardiac procedure in the first year of life to better understand the impact of CHD on children, families and health services. Methods and results: A population-based record-linkage cohort study was undertaken. Rate of cardiac procedures in the first year of life over the study period 2001–2012 in New South Wales, Australia, was steady at 2.5 children per 1000 live births, accounting for 2722 children. Excluding those with isolated closure of patent ductus arteriosus ( n  = 416), 50% required readmission in the first year of life. Over 1/5th had an additional non-cardiac congenital anomaly. Average total cost per infant for initial procedure admission was $67, 054 AUD ($63, 124–$70, 984) with a median length of stay (LOS) 13 days (IQR 8–23). Average cost per readmission in the first year of life was $11, 342 (95% CI 10, 361–$12, 323) with median LOS 2 days (IQR 1–5). Mortality rate in the 30 days following initial procedure was 3.1% (72/2306). Mortality rate by age 1 year was 7.1%, and 13.8% for those who had neonatal surgery. Conclusion: Risk of mortality in operatively-managed CHD extends beyond the immediate perioperative period. Children undergoing a cardiac procedure in their first year are often readmitted to hospital for both further planned procedures and unplanned reasons such as infection. These readmissions capture the significant impact of illness and pose substantial financial cost to the health system.